Sarkasme dalam Kampanye Pemilihan Capres 2024 di Media Sosial Tiktok - Restu Dwi Saputri, Finas; Nugrahani, Farida; Suparmin, Suparmin (GERAM, 2024)
This research focuses on identifying variations in sarcasm used in the 2024 presidential candidate election campaign on the social media platform TikTok, especially in the period August to October 2023. The aim of the research is to describe the various forms of sarcasm that appear in the videos. The method used is a qualitative approach with content analysis. The data collection process involves six steps, namely formulating the problem, sampling the selected data sources, creating analysis categories, registering the data sample, establishing data collection criteria, and interpreting the results. The validity of the data was verified through a pragmatic approach to ensure the credibility of the research. Research findings show that in the 2024 presidential election campaign on TikTok, there were various types of sarcasm, including the use of words or sentences that imply disappointment, unpleasant expressions, innuendo, and even direct attacks against certain candidates or groups.